An Hybrid Algorithm to Currency Recognition using Digital Image Processing and Feature Extraction - Kanwar, Shikha (International Journal of Advanced Science and Technology, 2019)
The digital image processing is used to manage and building up an advanced framework to perform digital image with the utilization of algorithms on computer. Digital image processing handling alludes to the control of a picture by methods for processor. An image is nothing but a mathematical function 2D f (x, y) where x and y are two horizontal and vertical coordinates[1]. In this thesis we work on currency recognition system by using Digital Image processing. Currency recognition the standout amongst the most critical applications in image processing. By contemplating the case of a bank, each now acknowledgment of the group is required where utilization of the device which comprise of ultraviolet light. The cash note to the device gives by the banker and endeavor to see if the serial numbers, watermark images and the notes various different qualities of are pertinent to get the money and check denomination validness[2] . This process increases the work of the banker. In its place if the our framework utilizes by the banker and automate his work, significantly more precise outcome will be get, for example, investment firms, shopping centers where this sorts of framework can be utilized. Simpler method for perceive the currency notes is required. The fundamental rule of this approach is to plan a programmed framework which can without much of a stretch perceive the currency and give a precise outcome. The outcome demonstrates that the expected framework gives the precise outcome when it is connected on given info images.